Tumour necrosis factor alpha promoter polymorphism, TNF-238 is associated with severe clinical outcome of falciparum malaria in Ibadan southwest Nigeria - Olaniyan, SA; Amodu, OK; Bakare, AA; Troye-Blomberg, M; Omotade, OO; Rockett, KA; Malariagen Consortium (Elsevier, 2016)
Tumour necrosis factor (TNF) – α has been shown to play an important role in the pathogenesis of falciparum malaria. Two TNF promoter polymorphisms, TNF-308 and TNF-238 have been associated with differential activity and production of TNF. In order to investigate the association between TNF-308 and TNF-238 and the clinical outcome of malaria in a Nigerian population, the two TNF polymorphisms were analysed using Sequenom iPLEX Platform. A total of 782 children; 283 children with uncomplicated malaria, 255 children with severe malaria and 244 children with asymptomatic infection (controls) were studied. The distribution of TNF-308 and TNF-238 genotypes were consistent with the Hardy-Weinberg equilibrium. Distribution of both TNF polymorphisms differed significantly across all clinical groups (TNF-308: p = 0.007; TNF-238: p = 0.001). Further tests for association with severe malaria using genotype models controlling for age, parasitaemia and HbAS showed a significant association of the TNF-238 polymorphism with susceptibility to severe malaria (95% CI = 1.43–6.02, OR = 2.94, p = 0.003237) The GG genotype of TNF-238 significantly increased the risk of developing cerebral malaria from asymptomatic malaria and uncomplicated malaria (95% CI = 1.99–18.17, OR = 6.02, p < 0.001 and 95% CI = 1.78–8.23, OR = 3.84, p < 0.001 respectively). No significant association was found between TNF-308 and malaria outcome. These results show thegenetic association of TNF-238 in the clinical outcome of malaria in Ibadan, southwest Nigeria. These findings add support to the role of TNF in the outcome of malaria infection. Further large scale studies across multiple malaria endemic populations will be required to determine the specific roles of TNF-308 and TNF-238 in the outcome of falciparum malaria infection.